Effects of Experience and Computer Proficiency on the Acceptance Behaviour of Accountants towards Usage of Cloud-Based Accounting Technology. A case of Nigerian Accountants - Olomiyete, Igbalawole Ayobami (Journal of Ecohumanism, 2024)
This paper examined the moderating role of experience and computer proficiency level on the factors of acceptance behaviour of Nigerian accountants towards the usage of cloud-based accounting technology. This study identified three factors influencing an accountant's willingness to adopt CBAT: its perceived usefulness, complexity or ease of use, and external influences such as pressure from professional associations and peers. Data were gathered through a survey questionnaire from 319 chartered accountants in an online-focused group. The analysis, conducted using structural equation modelling, reveals that all three factors - perceived usefulness, ease of use, and external pressure - have a significant and positive direct impact on an accountant's acceptance behaviour, confirming their influential roles in shaping adoption decisions, findings suggest that all direct relationships significantly positively affect acceptance behaviour. After that, experience and computer proficiency levels were introduced separately into the model as moderators. Conclusions of the analysis suggested that all hypothesised effects (except for H1a) moderate the relationships between the endogenous and exogenous variables of the model. Overall, this study observed that accountants recognise CBAT as highly useful and that the years of experience of the accountant, as well as his computer proficiency levels, are important factors that support their desire to adopt the cloud accounting tool.